Prenatal Lipid-Based Nutrient Supplements Affect Maternal Anthropometric Indicators Only in Certain Subgroups of Rural Bangladeshi Women. Issue 9 (20th July 2016) - Matias, Susana L; Mridha, Malay K; Paul, Rina R; Hussain, Sohrab; Vosti, Stephen A; Arnold, Charles D; Dewey, Kathryn G
Abstract: Background: Maternal undernutrition and low macro- and micronutrient intake and weight gain during pregnancy have been reported in Bangladesh. Objective: We aimed to determine the effects of lipid-based nutrient supplements for pregnant and lactating women (LNS-PL) on weight gain and midupper arm circumference (MUAC) during pregnancy. Methods: The Rang-Din Nutrition Study, a cluster-randomized effectiveness trial conducted in Bangladesh, enrolled 4011 pregnant women at ≤20 wk gestation who received either 60 mg Fe + 400 μg folic acid/d or 20 g LNS-PL/d (118 kcal) containing essential fatty acids and vitamins and minerals until delivery. At 36 wk gestation, women were interviewed at home and then attended a follow-up examination at local clinics ( n = 2877), where anthropometric measurements were taken. Results: No significant differences between intervention groups in maternal weight gain per week, low weight gain per week, or MUAC at 36 wk gestation were observed in the full sample. However, among multiparous women aged ≥25 y, those in the LNS-PL group gained 34 g/wk more than their counterparts in the iron and folic acid (IFA) group ( P = 0.001), whereas no differences were seen in the other parity/age subgroups. Women aged ≥25 y in the LNS-PL group had a 0.4-cm greater MUAC than their counterparts in the IFA group ( P = 0.003); no significant differences were observed in the other age groups. Among women whose height at baseline was in the lowest quartile of the distribution, those in the LNS-PL group had a 0.1–0.3-cm greater MUAC at 36 wk gestation than those in the IFA group ( P = 0.004–0.014). Conclusions: Lipid-based nutrient supplements provided during pregnancy did not affect maternal anthropometric indicators in the overall sample but increased MUAC among women aged ≥25 y and those with lower stature and weight gain among multiparous women aged ≥25 y. This trial was registered at clinicaltrials.gov as NCT01715038.